Regenerative endodontic treatment performed with platelet-rich plasma presents better periapical healing than only induced blot clot: a systematic review (Research, Society and Development, 2021)
This study comprehensively reviewed two different treatments for regenerative endodontic: platelet-rich plasma and induced blot clot, in regarding to periapical healing.  Two investigators performed a systematic review. MEDLINE/PubMed, Cochrane Library and Scopus supplied relevant data from studies published until December 2020 to answer the PICO question. Primary outcome was periapical healing. Eight randomized clinical trials fulfilled eligibility criteria. Primary outcome indicated that platelet-rich plasma results in similar or better periapical healing compared to blot clot group. The reported failures were related to blot clot group due to incomplete radiographic parameters, pain and reinfection; however, few cases of unsuccess were reported to platelet-rich plasma group. Only two studies observed better results to blot clot group in relation to increase of radiographic area and partial pulp canal obliteration. This review showed that procedures using platelet-rich plasma were successful in treating permanent teeth with root development.